2009
DOI: 10.2298/soc0902177p
|View full text |Cite
|
Sign up to set email alerts
|

Is there a sociodemographic model of acceptance of postmaterialist values?: The case of Serbia

Abstract: The paper offers an analysis of the factors of acceptance of postmaterialist values in Serbia. In accordance with the assumptions of Inglehart's postmaterialist value theory, but also on the basis of empirical works of his critics, the correlation between postmaterialist values and four sociodemographic variables: age, level of education, level of family income and population size of settlement, was analyzed. The data, collected in a 2007 public opinion research including 1410 citizens of Serbia aged 15-89, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
2
9
0
2
Order By: Relevance
“…Authoritarianism is a cognitive trait that arises on the basis of learned concepts that are prevalent in certain cultures or subcultures and presents a refl ection of the current conditions in which an individual is found because it is rational for the individual to be directed to power and to be obedient to the authorities in certain social circumstances (Greenstein 1987). Results gained in our research, which show that our sample characterizes a low level of authoritarianism, are in accordance with Inglehart's theory and his postmatialistic approach (Inglehart 1971;Inglehart, Flanagan 1987;Abramson, Inglehart 1992;Inglehart, Abramson 1999;Inglehart, Baker 2000), where it is emphasized that the manifested secular-rational and self-expression values are a refl ection of a culture in which survival is certain, thus refl ecting anti-discrimination and humanistic tendencies, and resistance to traditional norms and externally imposed authority (Pavlović 2009).…”
Section: Survey Results and Analysissupporting
confidence: 86%
See 2 more Smart Citations
“…Authoritarianism is a cognitive trait that arises on the basis of learned concepts that are prevalent in certain cultures or subcultures and presents a refl ection of the current conditions in which an individual is found because it is rational for the individual to be directed to power and to be obedient to the authorities in certain social circumstances (Greenstein 1987). Results gained in our research, which show that our sample characterizes a low level of authoritarianism, are in accordance with Inglehart's theory and his postmatialistic approach (Inglehart 1971;Inglehart, Flanagan 1987;Abramson, Inglehart 1992;Inglehart, Abramson 1999;Inglehart, Baker 2000), where it is emphasized that the manifested secular-rational and self-expression values are a refl ection of a culture in which survival is certain, thus refl ecting anti-discrimination and humanistic tendencies, and resistance to traditional norms and externally imposed authority (Pavlović 2009).…”
Section: Survey Results and Analysissupporting
confidence: 86%
“…Another author reached similar conclusions. Namely, in his research, on a representative sample of the Serbian population, Pavlović (2009) determined that 49% of respondents were characterised by materialistic values, and only 6% by postmaterialistic. Th ings are not diff erent when it comes to highly educated members ether, as the research conducted by Maksić and Pavlović (2012), based on data from the fourth wave of the EVS that was in Serbia conducted in 2008 on a representative sample shows.…”
Section: Survey Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Very similar results have been demonstrated in other representative surveys carried out in Serbia and western Balkans (Pavlović, 2009, Pešić, 2009, Petrović, 2011. By investigating the materialist and post-materialist orientations, Pavlović (2009) arrived to the conclusion that around 47% of the respondents represented a mixture of both.…”
Section: S O C I O L O G I J a I P R O S T O Rsupporting
confidence: 88%
“…Serbia's 2001 participation in the World Values Survey showed high esteem for the family, family authority and sacrifice for children. Moreover, it displayed a pattern of family attitudes and values based in an unreflective relationship to parent authority, an emphasis on diligence and responsibility as the most important personal characteristics, as well as a mild (in)acceptance of a different role for women (Pavlović 2007). A study of value systems within contemporary families in Serbia (Milić 2010) has showed that acceptance of modern attitudes is moderate, and that both men and women endeavor to maintain their traditional rights.…”
Section: Normative Aspects Of Gender Structures In Contemporary Serbiamentioning
confidence: 99%